Мефодий Буслаев. Танец меча: повесть / Дмитрий Емец; худ. И. Варавин - Емец Дмитрий Александрович (Мефодий Буслаев, 2011)
Экземпляры: ФО - 1; 3; 13; (20110303) / Инвентарный номер: 46704 / Цена: 177.60 / Сис.шифр: 84(2Рос=Рус)6 46704 / Авт.знак: Е 60 / ББК: 84(2Рос=Рус)6